As construções gráficas das funções do 1º, 2º grau, exponencial e logarítmica com a utilização do software GeoGebra - BARRETO, Rafael da Trindade (2022)
This work addresses how to understand the graphic constructions of 1st, 2nd degree, exponential and logarithmic functions using the GeoGebra software. We try to explain some properties of these functions and the graphic sketches with the help of GeoGebra. It will become possible to study the geometric behavior of each function, understanding the variations of the tabulated quantities for the realization of the graphic sketch. The steps are developed with the GeoGebra software, indicating a preliminary study with the use of tools, restricting the study only to the graphic constructions of the aforementioned functions. It is verified that the functions can be used in a contextualized way, the logarithmic and exponential functions, for example, can be drawn to reach visually approximate results of the growth and decrease curve of the number of deaths committed by the pandemic, but this work allows only to do this visual approximation, with the behavior of the number of deaths as a function of time in months, using the data will certainly obtain better results, but what this work proposes, already offers a better understanding of the curves traced in the Cartesian plane. It is concluded that it is important to use a resource to improve the methodology and research itself and, despite everything, it is necessary to understand that whatever the purpose, one cannot fail to understand mathematical knowledge, without which it can make understanding difficult. from the program.